2009
DOI: 10.17221/1105-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Antioxidant Capacity of Robusta Coffee during Roasting

Abstract: Abstract:The in vitro radical scavenging capacity of the roasted and ground coffee is generally known as well as the published results of lowering the incidence of various diseases by regular intake of coffee. The antioxidant capacity of coffee is based mainly on the phenols, but during the roasting phenols are degraded and new products with antioxidant capacity are formed. A major contributor to the antioxidant activity was identified as N-methylpyridinium, which is formed during the roasting by degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 7 publications
2
18
0
3
Order By: Relevance
“…They result from the combination of sugars and amino acids through the Maillard reaction or caramelization of carbohydrates. Progressive reduction in the antioxidant activity of the coffee brew was observed with the degree of bean roasting, showing the medium roasted coffee the highest activity, due to the balance between the degradation of phenolic compounds and the generation of Maillard reaction products during this process (Bekedam et al, 2008;del Castillo, Ames, & Gordon, 2002;del Castillo, Gordon, & Ames, 2005;Sacchetti, Di Mattia, Pittia, & Mastrocola, 2009;Votavová et al, 2009). Budryn and Nebesny (2008) found that extracts of Robusta coffee had higher antioxidative efficacy than those from Arabica coffee beans and, also, that the most efficient method for extraction of antioxidants was boiling ground coffee beans in water under elevated pressure.…”
Section: Roasted Coffeementioning
confidence: 99%
“…They result from the combination of sugars and amino acids through the Maillard reaction or caramelization of carbohydrates. Progressive reduction in the antioxidant activity of the coffee brew was observed with the degree of bean roasting, showing the medium roasted coffee the highest activity, due to the balance between the degradation of phenolic compounds and the generation of Maillard reaction products during this process (Bekedam et al, 2008;del Castillo, Ames, & Gordon, 2002;del Castillo, Gordon, & Ames, 2005;Sacchetti, Di Mattia, Pittia, & Mastrocola, 2009;Votavová et al, 2009). Budryn and Nebesny (2008) found that extracts of Robusta coffee had higher antioxidative efficacy than those from Arabica coffee beans and, also, that the most efficient method for extraction of antioxidants was boiling ground coffee beans in water under elevated pressure.…”
Section: Roasted Coffeementioning
confidence: 99%
“…Since coff ee contains signifi cant amounts of antioxidants and other positive active components, researchers have indicated the potential benefi cial health eff ects of coff ee (Mišik et al, 2010;Nicoli et al, 1997;Trandafi r et al, 2013). Svilaas et al (2004) and Votavova et al (2009) confi rmed that coff ee beverages contribute 66% of the total antioxidant intake. Recent studies have shown that coff ee components such as tocopherols, carotenoids, caff eine, phenolic compounds such as chlorogenic acid, hydroxycinnamic acid and products of the Maillard reaction, such as melanoides, have antioxidant properties (Parras et al, 2007;Vignoli et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…As trigonelline chemically changes to Nmethylpyridinium during the roasting process, it increases in AA, thus improving its TEAC (Votavova et al, 2009). Nicotinic acid produced by N-methylpyridinium shows promise as an anti-inflammatory agent, as it reduces MCP-1 and upregulates adiponectin in adipocytes infused with TNF-a (Digby et al, 2010).…”
Section: Trigonellinementioning
confidence: 99%